Hydro-implantation versus Visco-implantation of Intraocular Lenses and Fluid Load Effect on Corneal Endothelial Cells after Uneventful Phacoemulsification - Ibrahim, Mohamed Mohamed-Aly; Salama, Omar Hassan; Sofy, Mahmoud; Mohamed, Sanaa Ahmed; Elmahdy, Ahmed Gomaa (Open Access Macedonian Journal of Medical Sciences, 2022)
AIM: The purpose of the study was to study the effect of implantation method and fluid load (aspiration time, aspiration volume) on corneal endothelium in uneventful phacoemulsification surgeries. METHODS: This study was a prospective and interventional study involved 77 eyes, 50−81 years, divided into three groups according to implantation method (on Saline, Healon, or Methylcellulose). Specular microscope analysis of corneal endothelial parameters: Cell density (CD), central corneal thickness (CCT), coefficient of variation (CV), and Hexagonality (HEX) were done before and 3 months after surgery. RESULTS: A total of 77 eyes with cataracts were studied, and there was a significant increase in CCT and CV with a decrease in CD and HEX in all three groups. On comparing the same parameters between the three groups, there were insignificant differences regarding CCT and HEX changes. Although there was a significant change in CD, the highest loss was in the Healon group (median −0.138), followed by the Saline group (median −0.118), and the lowest was in the Methyl group (median −0.075). There was a significant change in CV, showing the highest increase in the Healon group (median 0.16129) followed by the Saline group (median 0.13307) and the lowest in the Methyl group (median 0.1266). There was a non-significant change in all corneal parameters among cases in each group with different aspiration volumes and times. CONCLUSION: Endothelial cell loss was lowest with Methyl followed by saline, and highest with Healon implantation. Fluidics had an insignificant effect in the three groups. Saline implantation was comparable to Healon, with an insignificant difference in CD loss.